Examining the Virtual Leadership of Leaders in Higher Education During the COVID-19 Pandemic: A Case Study - Guzar, Katlyn; Bianchi-Laubsch, Daniella (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation)

(untitled) (Department of Educational Administration, University of Saskatchewan, 2024)
During the COVID-19 pandemic, student services leaders needed to adapt to working entirely virtually, find creative solutions to adjust their service delivery, and change how they engaged with their teams. Before COVID-19, studies of virtual leadership focused on virtual teams developed because of the geographical distance between team members. This qualitative study investigated virtual leadership and virtual teams developed because of the move to virtual work during the COVID-19 pandemic. It examined how student services leaders changed their leadership behaviours in response to moving to the virtual work environment. Using data gathered through a questionnaire, interviews, and documentation, four themes reflecting how leaders changed their behaviours and practices were identified: reimagining communication, reconstructing work using technology, reframing team support, and reorienting toward hybrid work. Understanding how these leaders managed their virtual teams at a midsized university in southern Ontario provides insight into what practices might be helpful for teams that continue exclusively virtual work and those that transition to a hybrid work approach.